Milczące życie liter. O związku języka i przyrody w poezji R.S. Thomasa - Soćko, Joanna (Er(r)go. Teoria - Literatura - Kultura, 2014)
Joanna Soćko Silent Life of Letters. On Interconnections between Language and Nature in the Poetry of R.S. Thomas. The essay sets out to explore R.S. Thomas’ (1913–2000) vision of the problematic relations between the man, the nature and their Creator. In the context of contemporary critique as well as the 20th century, post-husserlian philosophy, the author analyses Thomas’ cosmological poems and represents, on the one hand, the place that both man and God take in the creation and, on the other, the sacramental relationship between the human and the nature. What is important from this perspective is the material existence of both man and nature, which enables mutual infiltration that leads to discovery of imperceptible dimension of materiality, which, in turn, influences both human consciousness and language. This is why the author asks about the role of science in Thomas’ poetry and about the influence that “the machine” has on language and consciousness.